Getting ahead of the storm: a look at severe weather and its impacts on our community. (1st October 2020) - Pecha, Hannah; Scott, Catherine
Abstract: Although severe weather has the potential to significantly impact people and the environment, it also presents unique opportunities to teach students about different weather phenomena and how to prepare. When our community was anticipating the hit of Hurricane Matthew, this was a great opportunity for students to become meteorologists and determine what may happen when Matthew made landfall. Engaging students in studying their local community and the natural world provides opportunities to for them to help solve real-world problems. In this lesson, inspired by the impending hurricane, we explored severe weather conditions and safety precautions as part of a larger study on weather systems. After completing research on severe weather, students identified the items needed in a severe weather kit and created a public service announcement for their community on what one should do during a severe weather event.